Language vitality of Malaysian languages and its relation to identity - How, Soo Ying; Chan, Swee Heng; Ain Nadzimah Abdullah, (Penerbit UKM, 2015)
Bahasa Malaysia is the national language in Malaysia, which acts as a national symbol that raise a sense of national unity, and maintains a sense of cultural value and identity. As the country is multicultural and multilingual, the use of Bahasa Malaysia, English, Mandarin, and Tamil invite questions of comparative vitality, which is a strength evaluation of language relative to other languages that coexist in the linguistic sphere.The present study, via the indicators such as language use, dominance and preference, language attitude and motivation, and language proficiency, aims to examine the vitality of these languages and to obtain comparative information about their connections to national and ethnic identity. Vitality Questionnaire was distributed to Malaysian primary five students fromvernacular Tamil and Chinese schools. Findings indicate that Bahasa Malaysiaand English do not have high vitality . Yet, vernacular languages are rated as having high vitality. It is suggested that ethnic languages dominantly shape ethnic identity and that they play animportant role in the students‟ lives at early age as compared to Bahasa Malaysia which has not gained a stronghold. Thus, the sense of national identity appears to have taken a back seat. National aspiration in this aspect of nation building is still far from being realized if it is to be nurtured and expected to be developed at this stage of growth. Within a multilingual milieu, establishing national identity appears a complex issue and language choice and use may have long term effects on the moulding of a Malaysian national identity.